Pengaruh persepsi kebermanfaatan dan kemudahan penggunaan e-samsat terhadap pembayaran pajak kendaraan bermotor di Kabupaten Bekasi - Jati Septiani; Whereson Siringoringo (JAAF (Journal of Applied Accounting and Finance), 2022)
The e-samsat application is an improvement from Bapenda service system in serving motor vehicle tax payments by Motor Vehicle Taxpayers. This study aims to determine the effect of taxpayers' perceptions of the usefulness and convenience of the e-samsat application as a factor that influences taxpayers in using the e-samsat application. This research use a quantitative method with the population Motor Vehicle Taxpayers who are registered in Samsat Bekasi Regency. The research results that taxpayers' perceptions of the usefulness of the e-samsat application have a positive effect on the use of e-samsat in motor vehicle tax payments, and taxpayers' perceptions of the ease of use of e-samsat applications have a positive effect on the use of e-samsat in Bekasi Regency.